Vibrotactile stimulation of the head enables faster gaze gestures. Issue 98 (February 2017) - Kangas, Jari; Rantala, Jussi; Akkil, Deepak; Isokoski, Poika; Majaranta, Päivi; Raisamo, Roope
Abstract: Gaze gestures are a promising input technology for wearable devices especially in the smart glasses form factor because gaze gesturing is unobtrusive and leaves the hands free for other tasks. We were interested in how gaze gestures can be enhanced with vibrotactile feedback. We studied the effects of haptic feedback on the head and haptic prompting on the speed of completing gaze gestures. The vibrotactile stimulation was given to the skin of the head through actuators in a sun glass frame. The haptic feedback enabled about 10% faster gaze gestures with more consistent completion times. Longer duration of haptic prompts tended to result in longer duration of gestures. However, the magnitude of the increase was marginal. Our results can inform the design of efficient gaze gesture user interfaces and recognition algorithms. Abstract : Highlights: The gaze gestures are completed faster when the haptic feedback is given. Haptic feedback reduces the variation in gaze gesture completion times. The duration of the haptic prompt affects the duration of the following gaze gesture.